Gender of Roles, Family Interaction, and Family Well-being in Single-Earner and Dual-Earner Families - Angraini, Sylvianti; Puspitawati, Herien; Muflikhati, Istiqlaliyah (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2024)
COVID-19 has had an impact on family life in both single-earner and dual-earner families. This study aims to analyze the effect of family characteristics, husband-wife gender roles, and family interaction on family well-being in single-earner and dual-earner families. This study was conducted in September 2021 and used a cross-sectional design with secondary data analysis from a family quality survey. Purposive sampling was used. The sample consisted of 986 families, namely families with an intact family type who had children, lived in DKI Jakarta, and had a single-earner or dual-earner status. Data were analyzed using an independent t-test and structural equation Modeling (SEM). The study found differences between single- and dual-earner families in the number of children, husband-and-wife education, family income, family interaction, and family well-being. Based on SEM analysis, in single-earner families, family well-being can be improved directly or indirectly by increasing family income, by achieving equality in husband-wife gender roles, and by improving good family interaction. In dual-earner families, family well-being can be directly improved by increased family income, equality of gender roles, and better family interaction. The conclusion was that families strive to increase income, establish gender equality, and interact well to improve family well-being.